Anti-microbial activity of seed oils & protein estimation of seed-content in Clitoria ternetea, Lagenaria siciraria & Ziziphus mauritiana - Sharma, Porshia; Rathore, Pragya; Choudhary, Yogesh; Tatwade, Yash; Joshi, Akshada (Brazilian Journal of Science, 2023)
Asian plants of flower, vegetable and fruit named Clitoria ternetea, Lagenaria siciraria and Ziziphus mauritiana respectively are known for their extensive uses in traditional medicine as well as traditional treatment of various diseases and infections. Several studies have already been done so far on these plants and its various parts but the studies on their seeds as well as their seed oilwas lacking. In this work, we determined the protein content of these seeds as well as we extracted the seed oils and determined their anti-microbial activity independently along with the anti-microbial activity by mixing all these oils together in equal ratios. Both, protein determination and anti-microbial activity determination showed considerable and potential results. The Lagenaria siciraria seeds (in ethanol extract) showed highest protein content amongst all i.e., 4.44 (μg/mL-1) whereas Clitoria ternetea seeds displayed highest protein content (in water extract) amongst all i.e., 5.07 (μg/mL-1). The anti-microbial activity of the mixed seed oil showed better and great results as compared to individual anti-microbial activity of seed oils.